THE IMPORTANCE OF ETHNOPEDAGOGICAL COMPETENCE FOR FORMATION OF PROFESSIONALISM FUTURE TEACHER - О.М. Tkachenko (Academy of Cognitive and Natural Sciences, 2008)
This article defines the role of ethnopedagogical competence in the development of a teacher's professionalism and emphasizes the importance of this type of pedagogical competence in the professional growth of a future specialist in the sphere o f education.